2015
DOI: 10.1186/s12931-015-0183-9
|View full text |Cite
|
Sign up to set email alerts
|

Denatonium inhibits growth and induces apoptosis of airway epithelial cells through mitochondrial signaling pathways

Abstract: BackgroundDenatonium, a widely used bitter agonist, activates bitter taste receptors on many cell types and plays important roles in chemical release, ciliary beating and smooth muscle relaxation through intracellular Ca2+-dependent pathways. However, the effects of denatonium on the proliferation of airway epithelial cells and on the integrity of cellular components such as mitochondria have not been studied. In this study, we hypothesize that denatonium might induce airway epithelial cell injury by damaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
4
12
0
Order By: Relevance
“…Our data on the inhibitory effect of the majority of the tested bitter avonoids on the proliferation of BECs are consistent with that of the canonical bitter tastant denatonium, as previously reported by Wen et al [5]. Additionally, these bitter avonoids exhibited inhibitory effect on the proliferation of BECs at a dose of a few hundred micromoles, which falls within the dosage level for the bitter tastant to be used to relax ASMCs [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data on the inhibitory effect of the majority of the tested bitter avonoids on the proliferation of BECs are consistent with that of the canonical bitter tastant denatonium, as previously reported by Wen et al [5]. Additionally, these bitter avonoids exhibited inhibitory effect on the proliferation of BECs at a dose of a few hundred micromoles, which falls within the dosage level for the bitter tastant to be used to relax ASMCs [25].…”
Section: Discussionsupporting
confidence: 91%
“…We rst analyzed the effect of denatonium on the proliferation of 16HBE14o-cells by cell counting (Figures S1A) and ATP luminescent assay ( Figures S1B). The result shows that denatonium inhibited the proliferation and decreased cell activity of the epithelial cells, which con rmed the data reported by Wen et al [5]. To explore bitter tastant that is not only useful for relaxation of ASMCs but also unharmful for proliferation of BECs, we rst focused on six bitter avonoids that are commonly used in both food and TCM and also known to alleviate asthma symptoms (Table S1).…”
Section: Naringin Promoted the Proliferation Of 16hbe14o-cellssupporting
confidence: 82%
See 1 more Smart Citation
“…The present results indicated that cowanin induced apoptosis via the mitochondrial pathway. As Bcl-2 is an antiapoptotic protein which binds with Bax and Bak to protect mitochondrial damage, the present results demonstrated that cowanin treatment decreased Bcl-2, leading to mitochondrial dysfunction and apoptosis (42).…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, many anticancer agents used in clinical therapy intervene with apoptotic signaling, either with the intrinsic or the extrinsic pathway [9,10].…”
Section: Introductionmentioning
confidence: 99%